Nivolumab versus chemotherapy in patients with advanced oesophageal squamous cell carcinoma refractory or intolerant to previous chemotherapy (ATTRACTION-3): a multicentre, randomised, open-label, phase 3 trial. Issue 11 (November 2019) - Kato, Ken; Cho, Byoung Chul; Takahashi, Masanobu; Okada, Morihito; Lin, Chen-Yuan; Chin, Keisho; Kadowaki, Shigenori; Ahn, Myung-Ju; Hamamoto, Yasuo; Doki, Yuichiro; Yen, Chueh-Chuan; Kubota, Yutaro; et al.
Summary: Background: Chemotherapy for patients with advanced oesophageal squamous cell carcinoma offers poor long-term survival prospects. We report the final analysis from our study of the immune checkpoint PD-1 inhibitor nivolumab versus chemotherapy in patients with previously treated advanced oesophageal squamous cell carcinoma. Methods: We did a multicentre, randomised, open-label, phase 3 trial (ATTRACTION-3) at 90 hospitals and cancer centres in Denmark, Germany, Italy, Japan, South Korea, Taiwan, the UK, and the USA. We enrolled patients aged 20 years and older with unresectable advanced or recurrent oesophageal squamous cell carcinoma (regardless of PD-L1 expression), at least one measurable or non-measurable lesion per Response Evaluation Criteria in Solid Tumors (RECIST) version 1.1, a baseline Eastern Cooperative Oncology Group performance status of 0–1, and who were refractory or intolerant to one previous fluoropyrimidine-based and platinum-based chemotherapy and had a life expectancy of at least 3 months. Patients were randomly assigned (1:1) to either nivolumab (240 mg for 30 min every 2 weeks) or investigator's choice of chemotherapy (paclitaxel 100 mg/m 2 for at least 60 min once per week for 6 weeks then 1 week off; or docetaxel 75 mg/m 2 for at least 60 min every 3 weeks), all given intravenously. Treatment continued until disease progression assessed by the investigator per RECIST version 1.1 or unacceptable toxicity. Randomisation was done using an interactive web response system with a block size of four and stratified according to geographical region (Japan vs rest of the world), number of organs with metastases, and PD-L1 expression. Patients and investigators were not masked to treatment allocation. The primary endpoint was overall survival, defined as the time from randomisation until death from any cause, in the intention-to-treat population that included all randomly assigned patients. Safety was assessed in all patients who received at least one dose of the assigned treatment. This trial is registered with ClinicalTrials.gov, number NCT02569242, and follow-up for long-term outcomes is ongoing. Findings: Between Jan 7, 2016, and May 25, 2017, we assigned 419 patients to treatment: 210 to nivolumab and 209 to chemotherapy. At the time of data cutoff on Nov 12, 2018, median follow-up for overall survival was 10·5 months (IQR 4·5–19·0) in the nivolumab group and 8·0 months (4·6–15·2) in the chemotherapy group. At a minimum follow-up time (ie, time from random assignment of the last patient to data cutoff) of 17·6 months, overall survival was significantly improved in the nivolumab group compared with the chemotherapy group (median 10·9 months, 95% CI 9·2–13·3 vs 8·4 months, 7·2–9·9; hazard ratio for death 0·77, 95% CI 0·62–0·96; p=0·019). 38 (18%) of 209 patients in the nivolumab group had grade 3 or 4 treatment-related adverse events compared with 131 (63%) of 208 patients in the chemotherapy group. The most frequent grade 3 or 4 treatment-related adverse events were anaemia (four [2%]) in the nivolumab group and decreased neutrophil count (59 [28%]) in the chemotherapy group. Five deaths were deemed treatment-related: two in the nivolumab group (one each of interstitial lung disease and pneumonitis) and three in the chemotherapy group (one each of pneumonia, spinal cord abscess, and interstitial lung disease). Interpretation: Nivolumab was associated with a significant improvement in overall survivaland a favourable safety profile compared with chemotherapy in previously treated patients with advanced oesophageal squamous cell carcinoma, and might represent a new standard second-line treatment option for these patients. Funding: ONO Pharmaceutical Company and Bristol-Myers Squibb.